2021
DOI: 10.3389/fnut.2021.667812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Bioactive Phenolic Compounds and Agricultural Sustainability of an African Leafy Vegetable Corchorus olitorius L.

Abstract: Corchorus olitorius L. is an African leafy vegetable of high nutritional interest. To assess its agricultural suitability to sustainable cultivation conditions and its potential benefits for human nutrition, its phytochemical content in response to conservation agriculture practices [i.e., no-tillage (NT) and cover crop maintenance] and low water regime were evaluated and compared with response under conventional agriculture management. Hydric stress and NT did not affect the content of antioxidant metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Phenolic acids are cyanidin and cyanidin glucosides from the bark and leaf of C. capsularis whereas astragalin, tolifolin, isoquercitin, and jugulanin come from C. olitorius leaves, as reported by researchers [ 47 , 48 ]. From the leaves of C. olitorius , a number phenolic compounds such as chlorogenic acid (383.9 mg/100 g FW), 3,5-dicaffeoylquinic acid (102.1 mg/100 g), quinic acid, gallic acid, protocatechuic acid, 4- O -caffeoylquinic acid, caffeic acid, 1,3-di- O -caffeoylquinic acid, feruloyl-quinic acids, and 4,5-di- O -caffeoylquinic acid were identified [ 47 , 49 ]. According to the literature, chlorogenic acid may be the most predominant antioxidant [ 45 , 47 , 50 ], whereas caffeoylquinic acids and dicaffeoylquinic acids have been reported to inhibit human low-density lipoprotein oxidation in vitro; there are limited studies investigating the effects in vivo [ 51 , 52 ].…”
Section: Bioactive Compounds In Jutementioning
confidence: 99%
See 3 more Smart Citations
“…Phenolic acids are cyanidin and cyanidin glucosides from the bark and leaf of C. capsularis whereas astragalin, tolifolin, isoquercitin, and jugulanin come from C. olitorius leaves, as reported by researchers [ 47 , 48 ]. From the leaves of C. olitorius , a number phenolic compounds such as chlorogenic acid (383.9 mg/100 g FW), 3,5-dicaffeoylquinic acid (102.1 mg/100 g), quinic acid, gallic acid, protocatechuic acid, 4- O -caffeoylquinic acid, caffeic acid, 1,3-di- O -caffeoylquinic acid, feruloyl-quinic acids, and 4,5-di- O -caffeoylquinic acid were identified [ 47 , 49 ]. According to the literature, chlorogenic acid may be the most predominant antioxidant [ 45 , 47 , 50 ], whereas caffeoylquinic acids and dicaffeoylquinic acids have been reported to inhibit human low-density lipoprotein oxidation in vitro; there are limited studies investigating the effects in vivo [ 51 , 52 ].…”
Section: Bioactive Compounds In Jutementioning
confidence: 99%
“…The leaves of C. olitorius contain flavanones (naringenin, naringin), flavones (cirsilineol and cirsiliol), flavones glycosides (apigenin, apegenin-7- O -glucoside), tolifolin (kaempferol-3- O - β -D-galactopyranoside), astragalin (kaempferol-3- O - β -D-glucopyranoside), and jugulanin (kaempferol- 3- O -β-L-arabinopyranoside) [ 47 , 53 ]. A number of researchers have reported that flavonoid glycosides, flavonol glucosides astragalin, quercetrin, isoquercitin, quercetin 3-galactoside, quercetin 3 glucoside, quercetin 3-(6 malonylglucoside) and quercetin 3-(6 malonylgalactoside), quercetin 3- O -galactoside (hyperoside), and catechin were identified from the leaves of C. olitorius [ 49 , 50 , 53 , 56 , 57 ]. The content of quercetin glycosides in C. olitorius leaves was 233 mg/100 g of FW, almost twice that of onion, another significant source of quercetin glycosides [ 52 ].…”
Section: Bioactive Compounds In Jutementioning
confidence: 99%
See 2 more Smart Citations
“…However, based on careful consideration of the pros and cons of different aquaponic system designs and the limited availability of financial and material resources, this research utilized a media-based design, also known as the flood-and-drain aquaponic system ( Figure 1). The African catfish, Clarias gariepinus , was the preferred fish for the aquaculture unit, while three common vegetables in Nigeria, Celosia argentea, Corchorus olitorius, and Ocimum gratissimum , were the preferred plants for the hydroponic unit based on their food and medicinal values (Guzzetti et al, 2021; Nganteng et al, 2022). This study aimed to compare the growth parameters of C. gariepinus raised in constructed recirculatory aquaponics to those of C. gariepinus raised in conventional fishponds.…”
Section: Introductionmentioning
confidence: 99%